EFEKTIVITAS YURISDIKSI MAHKAMAH INTERNASIONAL DALAM PENEGAKAN HUKUM HUMANITER TERKAIT KEJAHATAN PERANG DAN PEMINDAHAN PAKSA DI GAZA - Rifa'i, Iman Jalaludin; Yuhandra, Erga; Fathurrahman, Fathur; Akbar, Satria (Jurnal Ilmiah Dinamika Hukum, 2025)
The effectiveness of the jurisdiction of the International Court of Justice (ICJ) in enforcing international humanitarian law related to war crimes and forced displacement in Gaza faces complex challenges. Although the ICJ has international legal authority to adjudicate violations of international obligations, the implementation of ICJ decisions, in particular provisional measures that have been issued regarding Gaza, are often ignored by Israel. This non-compliance is further complicated by global political factors, especially the United States' support for the temporary relocation policy of Gazans which exacerbates patterns of forced displacement. This research uses a normative juridical method, with a focus on studying international legal norms, such as the 1945 Statute of the International Court of Justice, the 1949 Geneva Convention IV, and the 1998 Rome Statute. A conceptual approach is used to dissect the concept of the effectiveness of the ICJ's jurisdiction, while a case approach is applied in analyzing the application of the ICJ's jurisdiction to the post-2023 Gaza conflict. political domination of big countries. Therefore, strengthening the ICJ's jurisdiction requires effective compliance system reform and firmer political support from the international community so that the ICJ does not simply become a normative symbol.